PENGARUH PENGETAHUAN DAN PENGGUNAAN OBAT NYAMUK BAKAR DENGAN KEJADIAN ISPA PADA BALITA DI DESA REJUNO - Amelia Ni'matul Fajrianti; Retno Widiarini; Pipid Ari Wibowo (Jurnal Delima Harapan, 2022)
According to WHO (World Health Organization), that ± 13 million children under five in the world die every year and these deaths occur in developing countries in Asia and Africa. ARI is a group of diseases that cause the highest absenteeism compared to other diseases. Patients with ARI in Rejuno Village, Karangjati District in 2020 as many as 53 cases and in 2021 as many as 75 cases. This study aims to determine the effect of knowledge, use of mosquito coils, and cooking fuel with the incidence of ARI in Rejuno Village, Karangjati Ngawi. This study uses a quantitative method with a case control. The population in this study were 75 toddlers with a sample of 60 respondents consisting of 30 cases of ARI and 30 controls. The sampling technique in this study was simple random sampling. Data collection using questionnaires and observations were analyzed by chi-square test. The results showed that there was an influence between knowledge and the incidence of ARI, p-value : 0.036, OR: 3.596, 95% CI 1.21-10,63 and there was no effect between the use of mosquito coils with the incidence of ARI, p-value was obtained: 0.291, OR : 0,571 , 95% CI 0,20-1,62.